Attractors for Discretization of Ginzburg-Landau-BBM Equations (Journal of Computational Mathematics, 2001)
In this paper, Ginzburg-Landau equation coupled with BBM equation with periodic initial boundary value conditions are discreted by the finite difference method in spatial direction. Existence of the attractors for the spatially discreted Ginzburg-Landau-BBM equations is proved. For each mesh size, there exist attractors for the discretized system. Moreover, finite Hausdorff and fractal dimensions of the discrete attractors are obtained and the bounds are independent of the mesh sizes.
Keywords: Attractor; Spatially discreted; Ginzburg-Landau-BBM equations; Hausdorff and fractal dimensions.